Designing learning and development for return on investment - Foster, Carrie (Finance and financial management collection., 2017)
Learning practitioners have, for too long, been struggling to shift the perception of learning and development from a function that is a cost to the organization, to that of a function that is central to delivering value-added activities for the organization. The ability to deliver a return on investment is not about investing in good evaluation mechanisms, although this is important. It is imperative that the learning practitioner owns the numbers and works with financial metrics in order to bid for adequate resources and support the organization's strategic ambitions. This book offers a brief overview of both a theoretical and a practical framework. The theoretical underpinning provides an examination of how the theories and research about human and group dynamic processes and self-renewal can be utilized in intervention design. The emphasis is on the "self-renewal" ability of the individual and the facilitation of the movement of groups to improve the health and effectiveness of organizations in a sustainable way. The book also offers a practical framework of two fundamentals of intervention design: the Diagnostic Phase--understanding the nature of the situation and the issues involved; and the Evaluation Phase--aligning to organizational performance objectives. This book demystifies the process of calculating return on investment, examines how to use the formula, and explains how it is possible to use existing metrics to deliver a return on investment analysis and develop a commercial mindset by designing learning and development for return on investment.